Efektivitas Otak Anak Usia Dini dalam Mengenal Calistung - Zulfatun Anisah (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2017)
The introduction of calistung in AUD focuses on brain optimization of children. The child's brain has a trillion brain cells and trillions of brain-nerve cell connections. Brain nerves. influenced by the number of myelin that awakened at the age of 0-2 years which will determine the ability of abstract thinking, scientific thinking at the formal stage of operations. The backbone and cerebral cortex are the central nervous system for humans. the physical body of the child can be trained through mild exercise. Other parts of the brain in the form of cerebral cortex handle the functions of intellectual and language. Parents or nannies can provide stimulation as needed. The results suggest that children from families with high language intake received higher IQ scores at age three. So is the case with children who get more cognitive stimulation, they are more skilled in language activities. Age of AUD precisely began to learn to read if it has reached the mental age, ie 5-5.5 years.